Prevalence and drug susceptibility pattern of group B Streptococci (GBS) among pregnant women attending antenatal care (ANC) in Nekemte Referral Hospital (NRH), Nekemte, Ethiopia - Hylemariam Mihiretie Mengist; Olifan Zewdie; Adugna Belew; Regea Dabsu (BMC Research Notes, 2017)
Abstract Objective The main objective of this study was to determine the prevalence and drug susceptibility pattern of group B Streptococci (GBS) among pregnant women. The specific objectives include; (1) To determine the prevalence of GBS colonization among pregnant women (2) To determine the drug susceptibility pattern of GBS among pregnant women and (3) To identify associated risk factors with GBS colonization among pregnant women. Results The median age of the participants was 24.5 years (range 16–38) and 86% participants were urban residents. The total prevalence of maternal GBS colonization from vaginal swab culture was 12.2% (22/180). The prevalence of GBS colonization rate was significantly higher in those pregnant women above 37 weeks of gestation [AOR, 95% CI 2.1 (1.2, 11.6), P = 0.03] and married ones [AOR, 95% CI 3.2 (1.8, 11.6), P < 0.021]. Twenty (91%) of GBS isolates were sensitive to vancomycin and the highest resistance was observed against penicillin G (77.3%). The prevalence of GBS colonization in this study was significantly high and differed by gestational age and marital status. None of the GBS isolates were resistant to vancomycin but higher resistance was shown against Penicillin G.